A top-down approach for setting climate targets for buildings: The case of a New Zealand detached house - Chandrakumar C; McLaren SJ; Dowdell D; Jaques R (IOP Publishing Ltd, 2019)
Climate change mitigation requires the construction of low/zero-carbon buildings, and this is a challenge for designers. The use of Life Cycle Assessment (LCA) provides useful information to support eco-efficiency improvements and therefore, to reduce the climate impacts of building designs. However, it does not provide information about whether a proposed design aligns with achieving the global climate target of limiting global warming to below 1.5C or 2C. This study, therefore, introduces an LCA-based top-down approach for setting climate targets for the whole life cycle of buildings in terms of greenhouse gas emissions. It involves assigning a share of the 2C global carbon budget for 2018-2050 to a country, to the construction sector of the country, and finally to a building. The approach includes a stock model that accounts for the projected growth in the number of buildings and associated climate impacts in a country up to 2050. The proposed approach was applied to a detached house in New Zealand, the most common residential building type in the country; it was found that the climate target of a New Zealand detached house over a 90-year lifetime is 71 tCO2eq. This modelling approach has potential to guide designers and other interested stakeholders in development of building designs enabling the building sector to operate within a selected global climate target (such as the 1.5C or 2C target).